Ma’badong dalam Analisis Semiotika Roland Barthes - Rahmawati Haruna (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Ma’badong is one of the Toraja ethnic culture that is still carried out. Ma’badong is one of the rituals of the Rambu Solo’ which was originally performed by adherents of Aluk Todolo confidence. Tana Toraja culture is inseparable from the early belief that the Toraja Aluk Todolo (ancestral spirits adore). This study aims to determine the meaning of denotation, connotation and myth contained in cultural Ma’badong. This type of research is a qualitative study using Roland Barthes' semiotic analysis. The research results show that Ma’badong within the meaning of denotation is derived from the Toraja language Ma' means